RELAIBILITY ASSESSMENT OF THE SOIL-WATER-RETENTION FOR UNSATURATED SAND SOILS - Mohammed Shakir Mahmood; Mustafa Jamal Abrahim; Salah Mahdi Saleh (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
In this investigation, the soil-water-retention is described in the soil-water-characteristics-curve (SWCC). SWCC contains the data required to explain the unsaturated soils' mechanical behavior. The reliable findings of unsaturated sand soil tests and the impact of initial density on the hydraulic properties under various matric suction and net normal stresses are examined. The tests are carried out on a sample of soil from the northern region of Al-Najaf city, Iraq. The sample of soil has been disturbed and remolded in the cell of Oedometer device. A modified high-air-entry-disc-based Oedometer is used with accessories to control the air and water pressures to achieve the specific matric suction in the unsaturated test. Two sets of tested specimens are prepared, first, at 90% and second at 95% of the maximum dry unit weight from the standard Proctor experiment. Each set is performed for different matric suction under 200 and 400 kPa net normal stress. (SWCC) The soil water retention curve is affected by the application of net normal stress and initial density. There is a decrease in water volume change with wetting progress in unsaturated soil tests due to an increase in soil density.